2012
DOI: 10.1111/j.1600-0528.2012.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐demographic and behavioural inequalities in the impact of dental pain among adults: a population‐based study

Abstract: The impact of dental pain showed a social gradient. Inequalities between socio-economic groups found in this study should be taken into account, as the impact of dental pain leads to reduced daily activities and poor quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
4
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 26 publications
5
37
4
7
Order By: Relevance
“…These results suggest the reverse influence of schooling with tooth loss and consequently to OH-related QOL and corroborate studies that also reported the influence of schooling on the QOL of individuals [28,29]. In contrast, a study measured the impact of loss of upper anterior teeth on the QOL of 50 patients partially edentulous of their anterior teeth and found no relationship between number of missing teeth and schooling [30].…”
Section: Discussionsupporting
confidence: 71%
“…These results suggest the reverse influence of schooling with tooth loss and consequently to OH-related QOL and corroborate studies that also reported the influence of schooling on the QOL of individuals [28,29]. In contrast, a study measured the impact of loss of upper anterior teeth on the QOL of 50 patients partially edentulous of their anterior teeth and found no relationship between number of missing teeth and schooling [30].…”
Section: Discussionsupporting
confidence: 71%
“…Although many studies have observed that individuals reporting worse oral-health related quality of life belong to low income households [12, 14, 15, 3742], few studies have explicitly analysed the shape of the socioeconomic gradient [4]. …”
Section: Discussionmentioning
confidence: 99%
“…5,6 The conditions can be excruciatingly painful; associated with sleep disturbance, limited ability to work, and difficulty in performing everyday tasks. 7 Left untreated, exacerbating root canal infections can be an immediate threat to systemic health, with nearly 7000 hospitalizations per annum reported in the US alone. 8 Root canal infections thus pose a problem not only on the individual, but also on the community level.…”
mentioning
confidence: 99%